CASC5 is a potential tumour driving gene in lung adenocarcinoma. (13th April 2020) - Cui, Yuanbo; Zhang, Chunyan; Ma, Shanshan; Guo, Wenna; Cao, Wei; Guan, Fangxia
Abstract: Previous studies have shown that cancer susceptibility candidate 5 (CASC5) plays important roles in several types of cancer. But its expression and clinical significance in human pan‐cancer remain largely unclear. In the present study, we comprehensively analysed the expression profile and prognostic values of CASC5 in pan‐cancer across 33 cancer types based on the online TCGA analysis databases. CASC5 was found to be abnormally expressed in 16 types of cancer. In addition, dysregulated expression of CASC5 was closely associated with patient overall survival (OS) in kidney renal papillary cell carcinoma (KIRP), lung adenocarcinoma (LUAD), pancreatic adenocarcinoma (PAAD) and thymoma (THYM). By comparative analysis, we found that CASC5 was significantly up‐regulated in LUAD and predicted poor patient OS. High CASC5 expression was closely correlated with tumour advanced stages of patients with LUAD. Through GSEA based on the KEGG database, CASC5 was found to be closely related to DNA replication and microRNA regulation in LUAD. Functionally, knockdown of CASC5 could inhibit cell proliferation of LUAD cells in vitro, rather than affecting cell migration and invasion. Mechanistically, CASC5 promoted proliferation of LUAD cells by targeting miR‐139‐5p. Collectively, our findings reveal that CASC5 is a novel oncogenic gene in LUAD and may be a potential clinical target and (or) biomarker for this human malignancy. Significance of the study: In this study, we for the first time comprehensively analysed the transcriptional level and prognostic significance of CASC5 in human pan‐cancer across 33 cancer types using online TCGA databases. Our study indicates that CASC5 is aberrantly expressed in many tumours and is closely related to the patient overall survival of several tumour types. Our findings reveal that CASC5 is a novel oncogene in LUAD based on bioinformatic analysis and functional experiments. Mechanistically, CASC5 promoted LUAD proliferation by targeting miR‐139‐5p. Results of this study suggest that CASC5 is a potential clinical target and (or) biomarker for LUAD.